Religious beliefs as coping strategies: exploring the conceptualisation of hope in Islam - Mohd Nasir, Siti Aisyah; Borhan, Lihanna; Syed Azman, Syarifah Zafirah; Fauzi, Nur Afiqah; Shahril, Roziana (IIUM Press, 2022)
Hopelessness tends to correlate with suicidal behaviours. Beck Hopelessness Scale (BHS) has been claimed to have a good predictive value in predicting suicidality. However, the low rate of suicide in most Muslim nations as compared to non-Muslim nation indicates hopefulness may be a better variable to explain the low rate of suicidality among Muslims. As the BHS lacks this element of hopefulness, especially in integrating the role of religious beliefs as the source of hope to Muslims, the current paper proposes an initiative for BHS to be used in predicting suicidality among Muslims by exploring Quranic verses related to hopefulness. These verses are believed to be the source of strength, comfort and hope for Muslims in facing life difficulties and indirectly predicting the low suicide rate among Muslims.